Who are farm animal welfare conscious consumers?. Issue 12 (5th May 2020) - Boaitey, Albert; Minegishi, Kota
Abstract : Purpose: This paper aims to synthesize the literature on consumer preferences for farm animal welfare (FAW), with an emphasis on characterizing consumers based on their FAW preferences. The objective is to provide insights into the salient characteristics associated with animal welfare conscious consumers. Design/methodology/approach: The authors conduct a systematic review of the results of published research on consumer preferences for FAW. Approximately 350 papers were reviewed, and 52 were included in the analysis. Findings: The authors' review suggests that consumers are not homogenous in their preferences for FAW. The authors identify seven themes that enabled them to characterize consumers with higher FAW preferences. These themes (i.e. age, education and income, gender, country and cross-cultural differences, attitudes and consumer and citizen functions) are grouped under four main headings (socio-demographics, ethics and attitudes, product characteristics and public roles). Research limitations/implications: The authors' synthesis reflects the findings reported in the literature to this date; the identified characteristics may change with time as new evidence becomes available. Practical implications: The information collected in this article would be useful to farmers and food and non-food retailers interested in effective product differentiation and marketing strategies regarding FAW standards. It can also inform policymakers about the state of consumer concerns for FAW. Originality/value: To the best of authors' knowledge, this is the first study that attempts to develop a systematic profile of consumers based on their FAW preferences.